PENGARUH KEPEMIMPINAN KOLABORATIF KEPALA SEKOLAH DAN KOMPETENSI PEDAGOGIK TERHADAP KINERJA GURU SEKOLAH DASAR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The research problem of this study is the low perfomance of teachers in East Mesuji Sub-district. This study aims to analyze and determine the significant corelation between the colaborative leadership of school principals and the pedagogical competence on the performance of elementary school teachers. This research employed an ex-post facto design. The sample consist of 179 participants, including school participals and the teachers, who also represented the population of this research. The data were collected using a questionnaire based on a Likert-scale, which had been tested for the reliability and validity.The data analysis technique used in this study was multiple linear regression, calculated using SPSS program. The results showed that colaborative leadership of the school principals had a significant and negative effect om the performance of elementary school teaches. This indicated that the higher the teachers perception of colaborative leadership, the lower their performance. Meanwhile, the pedagogical competence did not have a significant effect of teachers' perfomance However, simultaneously, the collaborative leadership of school principals and pedagogical competence had a significant effect on the performance of elementary school teachers.